Religiosity, Spirituality, and Job Performance among Local Government Employees: The Mediating Role of Work Engagement - Yudiatmaja, Wayu Eko; Samnuzulsari, Tri; Malek, Jalaluddin Abdul (Journal of Governance, 2024)
This study examines the effects of religiosity and spirituality on employee's job performance, with the mediating effect of work engagement. Using a sample of 345 public servants within local government employees in Indonesia, this study reveals that employee performance is partially mediated by work engagement in its relationship only to religiosity. Work engagement is not only dispensable in enhancing employee performance but also mediates the effect of religiosity on job performance in the public sector. However, it does not work in the relationship between spirituality and job performance. The findings of this study contribute to the research body on employee performance in local government by improving the understanding of the influences of religiosity, spirituality, and work engagement on job performance. This study also offers an important policy insight for policymakers in the local governments to increase job performance among their employees.